Influence of blade angle distribution along leading edge on cavitation performance of a centrifugal pump. Issue 3 (15th January 2015) - Xu, Y; Tan, L; Cao, S L; Wang, Y C; Meng, G; Qu, W S
Abstract: The influence of blade angle distribution along leading edge on cavitation performance of centrifugal pumps is analysed in the present paper. Three sets of blade angle distribution along leading edge for three blade inlet angles are chosen to design nine centrifugal pump impellers. The RNG k-ϵ turbulence model and the Zwart-Gerber-Belamri cavitation model are employed to simulate the cavitation flows in centrifugal pumps with different impellers and the same volute. The numerical results are compared with the experimental data, and the comparison proves that the numerical simulation can accurately predict the cavitation performance of centrifugal pumps. On the basis of the numerical simulations, the pump head variations with pump inlet pressure, and the flow details in centrifugal pump are revealed to demonstrate the influence of blade angle distribution along leading edge on cavitation performances of centrifugal pumps.